Trends and inequalities in adequate antenatal care coverage among women in Sierra Leone, 2008-2019 - Augustus Osborne; Florence Gyembuzie Wongnaah; Medlin Soko Tucker; Camilla Bangura; Fatmata Gegbe; Bright Opoku Ahinkorah (BMC, 2024)
Abstract Background Prenatal care is a critical component of maternal and child health, providing essential preventive, diagnostic, and therapeutic services to pregnant women. Adequate antenatal care has been linked to reduced maternal and infant mortality and improved birth outcomes. Despite its importance, disparities in antenatal care coverage persist globally, including Sierra Leone, with significant implications for maternal and child health. This study examined the trends and inequalities in antenatal care utilisation in Sierra Leone. Methods We used data from the 2008, 2013, and 2019 Sierra Leone Demographic and Health Surveys. Simple inequality measures (Difference and Ratio) and complex measures (Population Attributable Risk and Population Attributable Fraction) were computed using the World Health Organization's Health Equity Assessment Toolkit software. Inequality in antenatal care was calculated on six stratefiers: age groups for women, birth order, educational levels, economic status, residential areas, and sub-national province. Results There was a significant increase in adequate antenatal care coverage from 2008 (15.2%) to 2013 (36.5%) but a decrease in 2019 (22.1%). The inequality in age increased over time from a Difference of 2.7 percentage points in 2008 to a Difference of 5.3 percentage points in 2019, indicating age-related inequalities. The Population Attributable Fraction decreased from 2.7% in 2008 to zero in 2013, indicating no further improvement in the national average of adequate antenatal care coverage can be achieved in the absence of age-related inequalities. However, it increased to 7.7% in 2019, indicating that the national average of adequate antenatal care coverage would have increased by 7.7% in the absence of age-related inequalities. The birth order inequality increased from a Difference of − 5.2 percentage points in 2008 to 2.6 percentage points in 2019. The Population Attributable Fraction was zero in 2008 and 3.4% in 2019, showing that the national average of adequate antenatal care coverage would have increased by 3.4% if there was no parity-based inequality. Inequality in economic status decreased from 32.1 percentage points in 2008 (Difference = 32.1) to 2.8 percentage points in 2019 (Difference = 2.8). The Population Attributable Fraction revealed that the national average could have been 164.4% higher in 2008 and 20.8% higher in 2013; however, it was zero in 2019, indicating that no further improvement can be achieved in the national average if there was no inequality related to economic status. Inequality for education decreased from 49.9 percentage points in 2008 (Difference = 49.9) to 11.0 percentage points in 2019 (Difference = 11.0). Inequality decreased from a Difference of 20.8 percentage points in 2008 to a Difference of 1.7 percentage points in 2019 for place of residence inequality, showing a reduction in inequality. Provincial inequality decreased from a Difference of 33.9 percentage points in 2008 to 8.5 percentage points in 2019. Conclusion While there have been notable improvements in antenatal care coverage in Sierra Leone, adequate antenatal care coverage is still below the WHO target of 78% in 2016, and significant inequalities persist. Addressing these inequalities requires a multifaceted approach considering demographic, economic, educational, and geographic indicators considered in this study. Sustained efforts and targeted interventions are critical by the Sierra Leone government to ensure that all women, regardless of their background, have access to essential antenatal care services up to at least eight visits.